2018
DOI: 10.1128/iai.00403-18
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Phosphatase and Deoxyribonuclease Are Required by Pseudomonas aeruginosa To Defend against Neutrophil Extracellular Traps

Abstract: Neutrophil extracellular traps (NETs) are produced by neutrophils as an innate immune defense mechanism to trap and kill microbial pathogens. NETs are comprised of ejected chromatin that forms a lattice structure enmeshed with numerous antimicrobial proteins. In addition to forming the structural backbone of NETs, extracellular DNA (eDNA) has membrane-disrupting antimicrobial activity that contributes to NET killing. Many pathogens produce secreted extracellular DNases to evade the antimicrobial activity of NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…Escaping NETs promotes spreading of pneumococci from the upper airways to the lungs and from the lungs into the blood stream during pneumonia 49 . Bacterial release of DNase and phosphatases contribute to defense against NETmediated killing of Pseudomonas aeruginosa, highlighting the role of manipulating enzymes in combating NETs by microorganisms 50 . In addition, the pneumococcal polysaccharide capsule protects from NET trapping, but is not required for resistance to NET-mediated killing ( Fig.…”
Section: Nets and Eets In Bacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Escaping NETs promotes spreading of pneumococci from the upper airways to the lungs and from the lungs into the blood stream during pneumonia 49 . Bacterial release of DNase and phosphatases contribute to defense against NETmediated killing of Pseudomonas aeruginosa, highlighting the role of manipulating enzymes in combating NETs by microorganisms 50 . In addition, the pneumococcal polysaccharide capsule protects from NET trapping, but is not required for resistance to NET-mediated killing ( Fig.…”
Section: Nets and Eets In Bacterial Infectionsmentioning
confidence: 99%
“…a Extracellular traps consisting of a DNA scaffold and granule proteins entrap and kill microorganisms6,7,14,152 . Certain pathogens have developed properties for escaping the physical entrapment by (b) encapsulation of bacteria to shield against traps 51 or (c) release of endonucleases to degrade the extracellular DNA scaffold leading to less efficient killing of bacteria49,50 .…”
mentioning
confidence: 99%
“…Several groups have shown that DNA is an efficient nutrient source of carbon, nitrogen and phosphate [12][13][14]. eDNA and the DNA within NETs induce the expression of a two-gene operon encoding a secreted phosphatase and deoxyribonuclease in P. aeruginosa [14,15]. These secreted enzymes target DNA and protect P. aeruginosa from DNA killing during exposure to neutrophil extracellular traps [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have shown that DNA is an efficient nutrient source of carbon, nitrogen and phosphate (1214). Extracellular DNA and the DNA within neutrophil NETS induces the expression of a 2 gene operon encoding a secreted phosphatase and deoxyribonuclease in P. aerugino sa (14,15). These secreted enzymes target DNA and protect P. aeruginosa from DNA killing during exposure to neutrophil extracellular traps (15).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular DNA and the DNA within neutrophil NETS induces the expression of a 2 gene operon encoding a secreted phosphatase and deoxyribonuclease in P. aerugino sa (14,15). These secreted enzymes target DNA and protect P. aeruginosa from DNA killing during exposure to neutrophil extracellular traps (15). These genes are also induced under phosphate limiting conditions, and also contribute to DNA degradation and phosphate acquisition when using DNA as a nutrient (14).…”
Section: Introductionmentioning
confidence: 99%